Environmental Cleanliness in Maintaining Public Health in Lapangan Merdeka Medan - Yasir Riady; Melisa Arisanty; Eko Kuswanti; Sri Sukatmi; Muhammad Firman Karim; Muhammad Ajmal (CV Media Inti Teknologi, 2025)
Background of the study: Environmental cleanliness is an important factor in maintaining public health and environmental sustainability.Purpose and scope of the paper: Students of Universitas Terbuka Medan play an active role in increasing public awareness through environmental cleanliness socialization activities carried out at Merdeka Square, Medan.Methods: The methods used in the socialization include counseling, waste management demonstrations, and clean-up actions involving the local community. The results of the activities show an increase in public awareness and participation in maintaining environmental cleanliness.Results: With this socialization, it is hoped that a sustainable culture of caring for the environment will be created among the people of Medan.Conclusion : Through adequate facilities, the active role of cleaners, and high public awareness, the cleanliness of Merdeka Square can be well maintained.